ZAKATECH : THE READINESS OF ISLAMIC ECONOMIC DEVELOPMENT IN NEW NORMAL ERA - Muhammad Syahbudi; R. Juli Moertiono (Proceeding International Seminar of Islamic Studies, 2021)
Readiness for the new normal era after the Covid 19 pandemic such as BAZNAS in the process of socialization, service and collection, such as ZakaTech which is expected to provide answers to zakat services that can help muzaki in meeting their needs. responsibility in paying zakat as an application of Islamic economics. ZakaTech as the development of zakat is also considered very crucial so that the benefits and impacts of zakat can be felt more by mustahik and the people who are affected by the economy. Based on this phenomenon, the authors analyzed the development strategy with the Interpretative Structural Modeling (ISM) approach. The strategy or core foundation needed in the ZakaTech development framework is the ability to manage and analyze data in the era of big data and human resources (AMIL) in digital services with a qualitative approach. The research results show that the goal of zakatech towards this new normal era is to formulate a technology-based zakat development strategy by strengthening the foundations of zakat institutions and the use of information technology nationally so that it is hoped that it will improve operational performance in the collection and distribution of zakat in Indonesia.Keyword : Zakatech, ISM, strategy and New Normal